Interpretative phenomenological analysis : theory, method and research - Smith, Jonathan A.; Flowers, Paul; Larkin, Michael, 1971- (Sage, 2009)
"This title presents a comprehensive guide to interpretative phenomenological analysis (IPA) which is an increasingly popular approach to qualitative inquiry taught to undergraduate and postgraduate students today."
Obsahuje bibliografii a rejstřík
Keywords: fenomenologická psychologie; psychologický výzkum; kvalitativní výzkum; psychologická metodologie; phenomenological psychology; psychological research; qualitative research; psychological methods; studie; studies